DISTRIBUTION MODEL AND ACCRUED STIMULATING ALLOWANCES IN A MEDICAL ORGANIZATION WITH A HEALTH CENTER IN ITS STRUCTURE - T. M. Maksikova; G. I. Gubin; A. N. Kalyagin (Acta Biomedica Scientifica)
This publication contains the universal model of the distribution of incentive bonuses in the medical organization, by the example of the structure containing a health center. Prepared algorithm of individual incentive bonuses presents the requirements for formulating criteria, and a form of the final protocol, painted traffic scheme documents is developed.